Rules and Reasoning: International Joint Conference, RuleML+RR 2017, London, UK, July 12-15, 2017, Proceedings - Costantini, Stefania; Franconi, Enrico; Van Woensel, William; Kontchakov, Roman; Sadri, Fariba; Roman, Dumitru (Lecture Notes in Computer Science, 2017)
This book constitutes the proceedings of the International Joint Conference on Rules and Reasoning, RuleML+RR 2017, held in London, UK, during July 2017. This is the first conference of a new series, joining the efforts of two existing conference series, namely "RuleML" (International Web Rule Symposium) and "RR" (Web Reasoning and Rule Systems). The 16 regular papers presented together with 2 keynote abstracts were carefully reviewed and selected from 29 submissions.The RR conference series has been a forum for discussion and dissemination of new results on all topics concerning Web Reasoning and Rule Systems, with an emphasis on rule-based approaches and languages. The RuleML conference series has been devoted to disseminating research, applications, languages and standards for rule technologies, with attention to both theoretical and practical developments, to challenging new ideas and industrial applications. Both series of conferences aimed at building bridges between academia and industry in the field of rules and their applications. Therefore, RuleML+RR is expected to become a leading conference for all subjects concerning theoretical advances, novel technologies, and innovative applications about knowledge representation and reasoning with rules.This new joint conference provides a valuable forum for stimulating cooperation and cross-fertilization between the many different communities focused on the research, development and applications of rule-based systems. It provides the possibility to present and discuss applications of rules and reasoning in academia, industry, engineering, business, finance, healthcare and other application areas.